AI DAN KRISIS NILAI: TELAAH PENDIDIKAN KARAKTER ISLAMI DALAM ERA TEKNOLOGI CERDAS - Intan Puspa Sari; Jeni Karisa Putri; Nadiya Cantika Rahayu; Hengki Satrisno; Deko Rio Putra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study investigates the moral challenges emerging from the rapid development of Artificial Intelligence (AI) within the context of Islamic Religious Education (PAI). The research is motivated by growing concerns related to declining empathy, reduced social interaction, digital dependence, and the spread of unverified religious information among students. The purpose of this study is to analyze the phenomenon of value degradation influenced by AI, identify potential moral risks, and formulate strategies for strengthening Islamic character education in the digital era. Using a descriptive qualitative approach with library research methods, data were collected from reputable books, journal articles, and academic reports published within the last five years. The data were analyzed through the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing, supported by triangulation of sources to test validity. The findings show that AI has ambivalent effects: it provides learning efficiency and digital access to Islamic resources, yet simultaneously weakens students’ reflective thinking, independence, spiritual awareness, and moral responsibility. The study also identifies critical risks such as misinformation, diminished self-control, erosion of discipline, and moral disorientation caused by excessive reliance on intelligent technologies. Furthermore, Islamic character education is found to play a strategic role in counterbalancing these risks through the reinforcement of core Islamic values, digital Islamic literacy, teacher role modeling, and ethical integration of AI in learning. The study concludes that strengthening Islamic character education is essential to prevent moral crises and guide students in using AI responsibly and ethically.